Water and Wastewater Services in the Danube Region : A State of the Sector - World Bank (Washington, DC, 2015)
This report analyzes the progress and challenges of 16 countries in the Danube watershed in delivering sustainable water and wastewater services to all, while meeting the European Union environmental acquis communautaire. After putting the services that are being delivered into context, the report analyzes the organization of services in the region and the level of access to services, that is, how well countries are doing in terms of providing access to water and wastewater services for the entire population. It then looks at the performance of the sector, including the quality of services provided and customer satisfaction with it. It also draws a picture of the efficiency of services, including whether they reflect accepted good practices. Finally, it analyzes the financing of services, looking at whether the financing of operation, maintenance, and investments is secured and affordable. The report draws largely from existing public data sources at the national and regional level, and consolidates them into a coherent, regional narrative, and analysis. The methods of analysis include horizontal comparisons among countries at a given point in time and trends within the countries or the region over a given period of time. Given shortcomings in the availability and comparability of data across 16 countries, the report seeks to encourage and inform a policy dialogue around sector challenges rather than provide a definitive set of policy recommendations.